D’Apprentice Bakery Cafe / Siyidah Raffhanah Basri... [et al.] - Basri, Siyidah Raffhanah; Blin, Nancy; Mohd Mazlan @Miden, Nurul Mazni; Marzuki, Munirah (2010)
D’ Apprentice Bakery & Cafe enterprise is a bakery with a cafe and will be the first bakery & cafe in Mukah new town area. The company with a slogan “Feed the day” is located at Sub lot 33, ground floor, Bandar Baru Mukah, Jin Org Kaya Setia Raja, 96400 Mukah. It not just selling variety of buns, bread and cake but also provided their customer with attractive, unique and comfortable cafe for their customer to fill their leisure time.To be in the market as a new comer is not that easy. However, D’Apprentice Bakery & cafe management team is very confident to exist in the market as they are not just a new comer who first established bakery with a cafe in Mukah town but they are also the beginner of introducing the new recipe, cupcake which is not yet in Mukah.The idea of d’ Apprentice Bakery & Cafe developed after realizing there are not yet bakery and cafe in Mukah even though there are already many bakery. The main thing that differentiates D’Apprentice Bakery & Cafe with other bakery in Mukah is the cafe for the bakery.Our main customer is resident in Mukah and also the comers from other places which majority are consist of students from UiTM Mukah and also Politeknik Mukah.Our main competitor is Honey Bakery House which has been the most popular bakery in Mukah since years ago. Besides that, our side-competitors are Azka Cake House and also Sweet Bun Bakery. While these entire bakery rapidly growth for their business, there are no doubt for D’Apprentice to exist in the market share as it has its own strengthens which is a bakery with a cafe.Lastly, management by professional and educated board of directors of the company and also expert bakers will be the special features and strength for D’Apprentice to present in the market.